Enhancing Students Listening Skills: The Impact of Podcast Integration in Language Learning - Putri, Ade Yustika; Abin, Rais; Suryadi, Ray; Pratiwi, Alifiah; Sultan; Syam, Hariadi; Naing, Ince Rezky (LifeSciFi, 2025)
This study aims to determine the effect of using podcasts on improving students' listening skills in learning English. Using a quasi-experimental design, two classes were involved, namely the experimental class that received learning through podcasts and the control class that was taught using conventional methods. The research instrument in the form of a multiple-choice test was arranged in the form of a pre-test and post-test to measure students' listening comprehension. The results of the analysis showed that students in the experimental class experienced a more significant increase in listening skills compared to the control class. This finding strengthens the theory of the importance of understandable input and Mayer's theory which emphasizes the combination of audio and verbal stimuli in learning. Podcasts have been shown to provide authentic input that can be accessed again according to the students' learning pace, thereby increasing their motivation, independence, and involvement in the learning process. Thus, podcasts are worthy of being used as an effective alternative learning media to improve listening skills in the context of teaching English as a foreign language.